A bidentate-anionic-group strategy for enhancing electron–phonon coupling and vibronic fluorescence in rare-earth crystals. Issue 30 (19th July 2022) - Feng, Jingcheng; Wang, Fangyan; Liu, Wang; Liang, Fei; Zhang, Guochun; Yu, Haohai; Zhang, Huaijin
Abstract : We found that the bidentate-BO3 group, better than the monodentate-BO3 unit, can greatly enhance the electron–phonon coupling and phonon-assisted fluorescence at longer wavelengths in rare-earth borates. Abstract : Electron–phonon coupling, representing the energy transfer between electron states and lattice vibrations, is a fundamental physical cornerstone for many interesting phenomena. Phonon-assisted electronic transition manifests as fluorescence emission, providing a good platform for studying electron–phonon coupling. Herein, we obtained K3 Gd(BO3 )2 and Li3 K9 Gd3 (BO3 )7 crystals and studied the relations of the coordination type between the central Gd 3+ ions and the [BO3 ] 3− ligand. Using Gd 3+ ions as a fluorescence probe, we found that the bidentate-BO3 group, better than monodentate-BO3, can greatly enhance the electron–phonon coupling and phonon-assisted fluorescence at longer wavelengths. Compared with K3 Gd(BO3 )2, the Huang–Rhys S factor of Li3 K9 Gd3 (BO3 )7 realized about triple improvement (from 0.057 to 0.163), which is attributed to the increased bidentate–BO3 ratio (from 50% in K3 Gd(BO3 )2 to 100% in Li3 K9 Gd3 (BO3 )7 ). More impressively, this bidentate-anionic-group strategy can be extended to rare-earth phosphates, in which KGd(PO3 )4 (without bidentate-PO4 ) and K3 Gd(PO4 )2 (with 50% bidentate-PO4 ) exhibit S factors of 0.08 and 0.133, respectively. These discoveries provide some potential fluorescence matrices and a helpful guideline for searching new rare-earth hosts with strong electron–phonon coupling for tunable broadband vibronic lasers.